Knowledge, Attitude and Practice regarding food hygiene among food handlers: A cross sectional study - Pokhrel, B; Pokhrel, KP; Chhetri, MR; Awate, RV; Sah, NK (Janaki Medical College Journal of Medical Science, 2016)
Background and objectives: Food is an important basic necessity, its procurement, preparation and consumption is vital for the sustenance of life. However, diseases that spread through food are common and persistent problems result in appreciable morbidity and occasionally in death. Eating establishments provide food on a large scale and are important from the point of view of epidemiology of food borne diseases in the community. This study is carried out to assess the Knowledge, Attitude and Practice (KAP) regarding food hygiene among food handlers working in food establishment in Nehru Nagar, Belgaum City.Material and Methods: A descriptive cross sectional study was conducted in food establishment in Nehru Nagar, Belgaum City. Sample is a subset of a population selected to participate in a study. Total number of food establishment’s functioning in Nehru Nagar is 103. . From each food establishment’s one cook, one helper and one service staff was selected randomly. Hence the total number of samples in the study is 103x 3= 309. Pre-tested structured questionnaire was used to gather information regarding practices of food hygiene. Data were coded and entered into SPSS sheet and analyzed by using SPSS software (SPSS 20.0 Version). Proportions were calculated wherever required from frequency tables. Chi square test was used.Results: The maximum number of subjects 251(81.2%) had average knowledge, 237 (76.7%) had average attitude and 262 (84.8%) had average practice. There is a statistically significant association found between demographic variables such as, nationality, religion, education, marital status, duration of employment, with knowledge of food handlers at the p < 0.05 level of significance.Conclusion: The food hygiene is an important aspect in food establishments made it compulsory for food handlers to provide clean food and free from contamination.Janaki Medical College Journal of Medical Sciences (2015) Vol. 3 (1):14-19